2014
DOI: 10.1097/ana.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Society for Neuroscience in Anesthesiology and Critical Care Expert Consensus Statement

Abstract: Literature on the anesthetic management of endovascular treatment of acute ischemic stroke (AIS) is limited. Anesthetic management during these procedures is still mostly dependent on individual or institutional preferences. Thus, the Society of Neuroscience in Anesthesiology and Critical Care (SNACC) created a task force to provide expert consensus recommendations on anesthetic management of endovascular treatment of AIS. The task force conducted a systematic literature review (up to August 2012). Because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 115 publications
2
58
0
8
Order By: Relevance
“…[ 16 ] Those studies which did suggest superior outcomes with CS speculated that the haemodynamic parameters such as hypocapnia and hypotension may lead to poor outcomes under GA[ 14 15 ] and thus recommend the maintenance of normocapnia (35–45 mmHg) and SBP in the range of 140–180 mmHg. [ 17 ] In our study, we found no evidence of difficulty maintaining SBP in these patients. Indeed, most of these patients were hypertensive at presentation and several needed antihypertensive agents to lower intraprocedural SBP.…”
Section: Discussionsupporting
confidence: 39%
“…[ 16 ] Those studies which did suggest superior outcomes with CS speculated that the haemodynamic parameters such as hypocapnia and hypotension may lead to poor outcomes under GA[ 14 15 ] and thus recommend the maintenance of normocapnia (35–45 mmHg) and SBP in the range of 140–180 mmHg. [ 17 ] In our study, we found no evidence of difficulty maintaining SBP in these patients. Indeed, most of these patients were hypertensive at presentation and several needed antihypertensive agents to lower intraprocedural SBP.…”
Section: Discussionsupporting
confidence: 39%
“…The Society for Neuroscience in Anesthesiology and Critical Care (SNACC) consensus statement opinioned that local anesthesia with anxiolytics can be used in neurologically cooperative patients for anterior circulation stroke who are able to protect the airway. 188 This recommendation lacked evidence from randomized trials. Similarly, endovascular coiling can be done for good grade ruptured aneurysms or unruptured aneurysms with local anesthesia with anxiolytics.…”
Section: Anesthesia For Coiling Embolizationmentioning
confidence: 99%
“…An expert consensus statement of the Society of NeuroInterventional Surgery and the Neurocritical Care Society[ 21 ] recommends the use of general anesthesia for patients with severe agitation, low level of consciousness (Glasgow coma scale <8), loss of airway protective reflexes, or respiratory compromise. [ 21 ] We preferred conscious sedation whenever possible. GA was administered in 59.9% of cases.…”
Section: Discussionmentioning
confidence: 99%